2020
DOI: 10.1007/s41403-020-00104-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Power Law Spread and Flattening of the Curve

Abstract: In this paper, we analyze the real-time infection data of COVID-19 epidemic for nine nations. Our analysis is up to May 04,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 29 publications
5
57
0
1
Order By: Relevance
“…The time series for both I(t) and D(t) follow exponential regimes during the early phases of the pandemic and subsequently transition to power-law regimes. This is in accordance with the earlier work of Verma et al [36] and Chatterjee et al [8]. The bestfit functions along with their relative errors are listed in Tables 1 and 2 for the infected and death cases respectively.…”
Section: Analysis and Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The time series for both I(t) and D(t) follow exponential regimes during the early phases of the pandemic and subsequently transition to power-law regimes. This is in accordance with the earlier work of Verma et al [36] and Chatterjee et al [8]. The bestfit functions along with their relative errors are listed in Tables 1 and 2 for the infected and death cases respectively.…”
Section: Analysis and Resultssupporting
confidence: 91%
“…We calculate the derivative using Python's gradient function and take a 5-day moving average in order to smoothen theİ(t) andḊ(t) curves. We observe that in the exponential regimes, the daily counts are proportional to the cumulative number of infected and death cases i.e.İ ≈ β i I andḊ ≈ β d D. Verma et al [36] show that power-law regime can be approximated as I(t) ∼ At n , and hence,İ ∼ I 1−1/n . Similarly, it can be shown that for power-lawsḊ ∼ D 1−1/n .…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…In this paper, we have proposed three regression models for the prediction of death cases by COVID-19 in Pakistan and selected quadratic modelling based on the model selection criterion. There are four stages of the epidemic, S1: exponential, S2: power law, S3: linear and S4: flat ( VermaAli, 2020 ). The death cases in Pakistan have entered the phase of balanced and quadratic regression in this term is giving an excellent fit to the data.…”
Section: Discussionmentioning
confidence: 99%
“…In the red circle, some of the countries that have been most infected. As several authors have already discussed [ 10 , 11 , 26 ], we think that the spatial diffusion of Covid-19 follows a power law. In fact, the plots in Fig 1(f) is calculated on a logarithmic scale, representing the number of infected people for the 217 countries and a ship, while the red curve of Fig 1(g) shows how a straight line intercepts this logarithmic distribution.…”
Section: Geo-spatial Diffusion Of Epidemicmentioning
confidence: 57%
“…Some authors have already investigated the infectious disease ecology, from the first mathematical modelling of infectious diseases of Bernoulli [ 4 ], to the Nobel Laureate Ross [ 5 ], to Kermack and McKendrick [ 6 , 7 ], just to cite a few examples. Some of them finding interesting correlations with power law expression [ 8 , 9 ], also for the Covid-19 disease [ 10 , 11 ]. Although we have models of the major currently known infectious diseases [ 12 ], such as HIV [ 13 ], malaria [ 14 ], SARS-coronavirus [ 15 ], rabies [ 16 ], and influenza [ 17 ], the unpredictable behaviour of SARS-CoV-2 has been unexpected.…”
Section: Introductionmentioning
confidence: 99%